Correlation between Electrochemical Impedance Spectroscopy and Structural Properties of Amorphous Tunisian Metanacrite Synthetic Material - Nouha Jaafar; Hafsia Ben Rhaiem; Abdessalem Ben Haj Amara (Advances in Materials Science and Engineering)
In the present work, we report the structural and electrochemical properties of metanacrite. Metanacrite is a synthetic material originated by heating (550°C) of a clay mineral (Tunisian nacrite) belonging to the kaolin group. The structure of the amorphous synthetic product was corroborated by X-ray diffraction (disappearing of nacrite peaks) and infrared spectroscopy (disappearing of Al–OH and water bands). The decomposition of the silicate framework was confirmed by transmission electron microscope (TEM). The obtained metanacrite synthetic material was also examined by electrochemical impedance spectroscopy (EIS). Accordingly, the electronic conduction is followed by the correlated barrier hopping (C.B.H.) model. Therefore, by combining ac and dc electrical conductivity, a semiconductor behavior is evidenced. The dependence of the dielectric constant (ε′) and dielectric loss (ε″) on both temperature and frequency is also discussed.